Bioinformatics Analysis of Quercetin and Morin Bioactivity from Morinda citrifolia L. Targeting Streptococcus mutans Virulence Factors In Dental Caries Cases - Astrid Ekklesia Saputri; Rian Ka Praja; Agnes Frethernety; Oktaviani Naulita Turnip; Ysrafil Ysrafil (Biology, Medicine, & Natural Product Chemistry, 2026)
Dental caries remains one of the most neglected oral diseases, particularly among populations living far from healthcare services. Its pathogenesis is largely triggered by poor oral hygiene and the activity of Streptococcus mutans. The use of synthetic antimicrobial agents often leads to prolonged side effects and a higher risk of antibiotic resistance. As an alternative, Morinda citrifolia L. extract shows high potential due to its good public acceptance, minimal side effects, and proven in vitro efficacy in inhibiting S. mutans growth. This study aimed to investigate the bioactivity factors of S. mutans in relation to specific components of Morinda citrifolia L. as an alternative therapeutic agent for dental caries using a bioinformatics-based approach. A descriptive-exploratory bioinformatics method was employed using computational analysis. The bacterial FASTA sequence of Streptococcus mutans UA159 was retrieved from the National Center for Biotechnology Information (NCBI) database and analyzed using several software tools, including STITCH v5.0, VICMPred, VirulentPred, BepiPred v1.0, MHC I and MHC II BindingPred, and PSORTb v3.0. The analysis revealed notable interactions in bioactivity between S. mutans proteins and the phytocompounds quercetin and morin. Seven virulent proteins PknB, SMU_1806, SMU_1213c, SMU_922, SMU_906, SMU_525, and SMU_1078c, contribute to cellular process, metabolism, virulence factors, and information & storage. Five proteins were identified in the cytoplasmic membrane, one in cell wall, and also cytoplasm. Quercetin and morin demonstrated strong antibacterial potential against S. mutans through interactions with virulent proteins. PknB, SMU_906, and SMU_1078c stand out in epitope T cell analysis with high affinity, demonstrating the ability to provoke an adaptive immune system response. Location complexity of 5’-nucleotide enzyme targeted by strategic antimicrobials leads to bacterial mortality.